2021
DOI: 10.1177/07395329211047009
|View full text |Cite
|
Sign up to set email alerts
|

Social media users (under)appreciate the news: An application of hostile media bias to news disseminated on Facebook

Abstract: News outlets rely on social media to freely distribute content, offering a venue for users to comment on news. This exposes individuals to user comments prior to reading news articles, which can influence perceptions of news content. A 2 × 2 between-subject experiment (N = 690) tested the hostile media bias theory via the influence of comments seen before viewing a news story on perceptions of bias and credibility. Results show that user comments induce hostile media perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
2
3
0
2
Order By: Relevance
“…The goal of the current study was to investigate how exposure to Facebook user comments can influence news audience perceptions of actual news content. Previous studies have investigated the influence of comments across controversial topics (Arceneaux et al, 2013;Kim, 2015;Gearhart et al, 2021). This project aimed to broaden the theoretical scope by testing whether different parts of the online news experience, like the inclusion of opinionated commentary before reading a neutral news story across different topics, influence one another rather than working in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of the current study was to investigate how exposure to Facebook user comments can influence news audience perceptions of actual news content. Previous studies have investigated the influence of comments across controversial topics (Arceneaux et al, 2013;Kim, 2015;Gearhart et al, 2021). This project aimed to broaden the theoretical scope by testing whether different parts of the online news experience, like the inclusion of opinionated commentary before reading a neutral news story across different topics, influence one another rather than working in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there is an urgent need for research focusing on user-generated comments paired with online news. User comments may influence perceptions due to the ability of third-party audience members to shape others' perceptions of a news story or its editorial frame and may ultimately contribute to perceptions of an implied lean to the story depending on the audience's pre-conceived sentiments (Gearhart et al, 2021). Moreover, studies found that user comments may exaggerate elements that appear within news segments and may further guide certain cognitive processes (Lee and Tandoc, 2017).…”
Section: Literature Review Theoretical Foundation: Hostile Media Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha demostrado, por ejemplo, que la existencia de comentarios contrapuestos acerca del contenido de una noticia en Facebook, incide de forma variable en la probabilidad de que otros usuarios presten atención sobre estas opiniones, compartan el post o hagan clic en el enlace adjunto (Dutceac Segesten, Bossetta, Holmberg, & Niehorster, 2020). También se ha visto que influyen en la percepción hacia el medio de comunicación, aun sin haber leído antes el contenido de la noticia (Gearhart, Moe, & Holland, 2021).…”
Section: Las Narrativas De Las Noticias Digitalesunclassified
“…Di sisi lain, penekanan dalam landasan model bisnis termasuk dalam bisnis media adalah menjalin hubungan dengan pelanggan (Osterwalder & Pigneur, 2010) Pada akhirnya menjalin kedekatan antara media dengan audiens dalam platform media sosial kini semakin mutlak dilakukan karena merupakan wadah penyampaian konten serta membangun interaksi dengan audiens/pengguna (Gearhart et al, 2021). Dalam lanskap media yang terus berubah, media harus adaptif seraya intens menjalin interaksi sosial dengan membina dan meningkatkan ikatan sosial dengan khalayak melalui pemanfaatan teknologi informasi dan komunikasi (Torro et al, 2022).…”
Section: Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik Dan Ko...unclassified